Comparison of Thermal and Hydrotime Requirements for Seed Germination of Seven Stipa Species From Cool and Warm Habitats - Zhang, Rui; Luo, Kai; Chen, Dali; Baskin, Jerry; Baskin, Carol; Wang, Yanrong; Hu, Xiaowen (Frontiers in Plant Science, 2020)
Temperature and water potential are two important environmental factors influencing germination and subsequent seedling establishment. Seed germination requirements vary with species and with the environment in which the seeds are produced. Stipa species dominate large areas of the Eurasian zonal vegetation, but comparisons of germination requirements between Stipa species from different habitats is limited. We investigated the effects of temperature and water potential on seed germination of S. grandis, S. purpurea and S. penicillata from habitats with low temperatures and relatively abundant rainfall (cool habitats) and S. glareosa, S. breviflora, S. gobiea and S. bungeana from habitats with relatively high temperatures and low amount of rainfall (warm habitats). Seeds of species from cool habitats had a higher base (Tb), optimal (To) and maximum (Tc) temperature than those of species from warm habitats, except for the base temperature of S. purpurea. Response of six tested Stipa species to water potential differed among species but not between habitats. Median water potential for germination as lowest for S. bungeana, S. penicillata and S. gobiea. There was a negative correlation between hydrotime constant (θH) and base water potential for 50% of the seeds of all species to germinate (ψb(50)). Germination time of seven Stipa species in response to temperature and water was well predicted by thermal time and hydrotime models. The results of present study are the likely consequence of climate change on germination of these seven species of Stipa, which may provide useful suggestions for grassland restoration in different habitats.